Examining the Web Design and Quality of Information to User Satisfaction : The Case of Student at Sekolah Tinggi Ilmu Ekonomi INABA Bandung - Evan Yuri Priambodo (Garuda Prestasi Nusantara Consulting, 2021)
This study aims to see how user satisfaction with website services in terms of aspects of web design and quality of information. The first hypothesis in this study is that there is a positive and significant influence between web design on user satisfaction with website services at the Sekolah Tinggi Ilmu Ekonomi INABA Bandung. The second hypothesis in this study is that there is a positive and significant influence between web design on user satisfaction with website services at the Sekolah Tinggi Ilmu Ekonomi INABA Bandung. The population in this study were students in Class A of the Sekolah Tinggi Ilmu Ekonomi INABA Bandung, amounting to 39 people. The sampling method was carried out by total sampling. Data were collected through questionnaires and analyzed using multiple regression methods. The results showed that web design has a positive and significant influence on user satisfaction with website services at the Sekolah Tinggi Ilmu Ekonomi INABA Bandung. The quality of information has a positive and significant effect on user satisfaction with website services at the Sekolah Tinggi Ilmu Ekonomi INABA Bandung. The quality of information has the most dominant influence on user satisfaction at the Sekolah Tinggi Ilmu Ekonomi INABA Bandung Keywords:web design, quality of information, user satisfaction